Correlates of Northern Bobwhite Distribution and Abundance with Land-Use Characteristics in Kansas - Stephen J. Brady; Curtis H. Flather; Kevin E. Church; Eric W. Schenck (National Quail Symposium Proceedings, 2017)
County-level agricultural statistics were correlated with Rural Mail Carrier Survey reports and Breeding Bird Survey data for northern bobwhite (Colinus virginianus) in Kansas. Results indicate statewide analysis is feasible when temporally congruent data exist for both agricultural land-use characteristics and bobwhite distribution and abundance. Interpretations of these results can be useful in state or regional analysis and in the development of habitat management strategies for bobwhite. The Multiple Response Permutation Procedure identified 16 land-use variables, 3 soil variables, and 1 spatial variable that were significantly different in counties where bobwhite were present from counties where they were absent. Sixteen land-use variables, 5 soil variables, and 3 spatial variables distinguished between counties where bobwhite abundance was classified as high or low. Spearman's rank correlation identified 8 soil variables, 14 land-use variables, and 3 spatial variables that were significantly correlated with bobwhite abundance. Least absolute deviation regression analysis revealed 4 land-use variables that were significantly correlated (Agreement= 0.48, P = 0.0001) with bobwhite abundance.
Keywords: abundance; agriculture; Colinus virginianus; distribution; Kansas; landuse; northern bobwhite